We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
218
1
avatar

If a + b + c = -1 and x + y = 7,

what is  -9a - 7x - 9c - 9b - 7y?

 Aug 31, 2018
 #1
avatar+7598 
+1

-9a - 7x - 9c - 9b - 7y

                                          Numbers can be added in any order, so we can rearrange the expression.

=   -9a - 9b - 9c - 7x - 7y

                                          Factor  -9  out of the first three terms and  -7  out of the last two terms.

=  -9(a + b + c) - 7(x + y)

                                          Substitute  -1  in for  a + b + c  and substitute  7  in for  x + y .

=  -9( -1 ) - 7( 7 )

 

=  9 - 49

 

=  -40

 Aug 31, 2018
edited by hectictar  Aug 31, 2018

23 Online Users

avatar